2015
DOI: 10.1016/j.ijpe.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

From sustainability commitment to performance: The role of intra- and inter-firm collaborative capabilities in the upstream supply chain

Abstract: Organisations increasingly see sustainability as an important element of their business strategies, and the role of purchasing and supply functions is critical in translating sustainability commitment into performance. Yet, the impact of sustainability commitment on purchasing processes and routines, as well as the effect of such capabilities on performance, remains empirically under-explored. From a Resource-Based perspective, we argue that commitment to sustainability leads purchasing and supply functions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 127 publications
(178 reference statements)
4
121
0
14
Order By: Relevance
“…In this approach, farmers are guided to abandon cheap but contaminated fertilizers and pesticides they used in the past when they were strapped for cash and turn to environmentally friendly products such as Chia Tai fertilizer for planting and breeding. This outcome shows that SCF is an effective incentive to enhance supply chain cooperation and improve the environmental performance of the entire supply chain [39].…”
Section: Environmental Aspectmentioning
confidence: 81%
See 3 more Smart Citations
“…In this approach, farmers are guided to abandon cheap but contaminated fertilizers and pesticides they used in the past when they were strapped for cash and turn to environmentally friendly products such as Chia Tai fertilizer for planting and breeding. This outcome shows that SCF is an effective incentive to enhance supply chain cooperation and improve the environmental performance of the entire supply chain [39].…”
Section: Environmental Aspectmentioning
confidence: 81%
“…Although an increasing number of organizations take sustainability as a crucial part of their business strategy [1,37,39], the analysis of sustainable operations focuses mainly on individual dimension sustainability, whereas complex sustainability perspective is insufficient [38,40].…”
Section: Sustainability and Agricultural Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this paper found that there is a strong relationship between perceived environmental responsibility and green products purchase willingness, there is no relationship between perceived seriousness of environmental problems and undergraduate students' green product purchase willingness and there are significant relationships between students' willingness to purchase green products and their green purchase behavior. Luzzini, Brandon-Jones [264] found there is lack of focus in previous studies in relation of sustainability commitments on development of collaborative capabilities for supply functions and purchasing on sustainability performance; therefore, this study examined the relationship between sustainability commitment, collaborative capabilities and performance. The finding of this paper showed that there is a link between sustainability commitment and collaborative capabilities, cost performance and social and environmental performance.…”
Section: Breakdown Of Articles Based On Other Green and Sustainable Omentioning
confidence: 99%